Mobile phone dependency and adolescent exercise participation: a CB-SEM and fsQCA study on the roles of self-control, time management, and health awareness - Quan Zhang; Cong Li; Jianxin Liu (Frontiers in Psychology)
ObjectiveThe study examined how mobile phone dependency (MPD) is linked to adolescents’ engagement in structured exercise and whether this association operates through three theoretically derived mechanisms—self-control (SC), time management (TM), and health awareness (HA). A complementary configurational analysis explored alternative combinations of these factors that lead to high or low exercise participation.MethodsA cross-sectional survey was administered to 1,404 Chinese students in Grades 5–9 (49.6% girls; 51% rural). Standardized scales assessed MPD, SC, TM, HA, and adolescent exercise participation (AEP). Covariance-based structural equation modeling (CB-SEM) estimated direct and mediated effects; bias-corrected bootstrap confidence intervals tested indirect paths. Fuzzy-set qualitative comparative analysis (fsQCA) identified sufficient configurations of conditions for high and non-high AEP and assessed robustness across calibration thresholds.ResultsThe SEM model exhibited excellent fit (χ2/df = 2.723, CFI = 0.979, TLI = 0.975, SRMR = 0.036, RMSEA = 0.035, 90% CI [0.031, 0.039]). MPD showed a significant total effect on AEP (β = −0.61, p < 0.001), of which 83.5% was transmitted through the three hypothesized mediators. Among single mediators, HA accounted for the largest share of the indirect effect (β = −0.15), followed by SC (β = −0.12) and TM (β = −0.03). Three two-step and one three-step chained paths were also significant (p < 0.01). FsQCA revealed three sufficient configurations for high AEP: (a) low MPD + high SC + high HA, (b) low MPD + high TM + high HA, and (c) high SC + high TM + high HA irrespective of MPD. One configuration—high MPD combined with low SC, TM, and HA—was sufficient for non-high AEP. All solutions were robust to parameter changes.ConclusionMobile phone dependency undermines adolescent exercise primarily by eroding self-regulatory capacity, disrupting time structure, and diminishing health motivation. Nonetheless, strong personal resources can offset the risks of heavy phone use. Interventions should therefore adopt a dual focus: curbing excessive smartphone use while simultaneously enhancing self-control, time-management skills, and health awareness to sustain youths’ exercise involvement.